1993
DOI: 10.1111/j.1525-1594.1993.tb03181.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Artificial Placenta: Survival of Isolated Goat Fetuses for Three Weeks with Umbilical Arteriovenous Extracorporeal Membrane Oxygenation

Abstract: The purpose of our study was to examine the feasibility of long-term extrauterine incubation of an isolated premature fetus in artificial amniotic fluid with arteriovenous extracorporeal circulation. Two premature goat fetuses (age 120 and 128 days) were incubated in an isothermal artificial amniotic fluid incubator with arteriovenous extracorporeal membrane oxygenation via the umbilical vessels. We administered pancuronium bromide to suppress fetal movement and swallowing because movement and swallowing have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 10 publications
2
55
0
1
Order By: Relevance
“…PO2 values of UA and UV in the goat fetus are known to range from 17.3 to 24 mmHg and from 30 to 33 mmHg, respectively. Fetal baseline data shown in Table 1 are in agreement with those of previous studies (4,9). PCO2 values were higher than normal values probably due to the higher CO2 production in the room air outside the uterus.…”
Section: Discussionsupporting
confidence: 82%
“…PO2 values of UA and UV in the goat fetus are known to range from 17.3 to 24 mmHg and from 30 to 33 mmHg, respectively. Fetal baseline data shown in Table 1 are in agreement with those of previous studies (4,9). PCO2 values were higher than normal values probably due to the higher CO2 production in the room air outside the uterus.…”
Section: Discussionsupporting
confidence: 82%
“…The use of an artificial placenta has been proposed, but previous studies have had limited success, possibly because the circuit volume was too large and the resistance of the circuit was too high (1)(2)(3)(4)(5). A more compact circuit may be a solution; in 2009, Reoma et al reported a 4-h survival period using a pumpless artificial placenta for the first time (6).…”
mentioning
confidence: 99%
“…The details o f the extrauterine incubation system o f an isolated goat fetus have been reported by Kuwabara and co-workers [10,11], In brief, a cesarean section was performed under general anesthesia with 4% halothane. Fetal hind legs were extracted and the umbilicus was fully exposed.…”
Section: Methodsmentioning
confidence: 99%